The Effect Of Product Quality, Brand Image, And Price On Purchase Decisions At Roti Laris 18 Bakery & Cake Pontianak - Pratamadilla, Intannia Feronika; Fachri, Helman (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The bread and cake industry in Pontianak, particularly establishments such as Roti Laris 18, encounters significant rivalry within an expanding market. This research examines the impact of product quality, brand image, and pricing on consumer purchasing choices for Roti Laris 18 Bakery Cake goods. As customer tastes evolve towards healthier and more sanitary food options, product quality significantly influences purchasing decisions. The study employs an associative methodology, employing purposive sampling to collect data from 100 participants who have purchased items from Roti Laris 18. The study used SPSS 25 software to do multiple linear regression and tests for validity, reliability, normalcy, linearity, and multicollinearity. The hypothesis testing incorporated both simultaneous testing (F-test) and partial testing (T-test). This study's findings indicate that product quality, brand image, and price significantly and positively influence customer buying choices, both collectively and independently. The statistics demonstrate that product quality significantly affects purchase intentions, although brand image and pricing both favorably impact customer decisions. The study's results correspond with current research, indicating that when companies synchronize product quality, brand image, and price tactics, they are more likely to affect purchase patterns and enhance market share. This study offers significant insights for Roti Laris 18 to enhance their marketing efforts. It is advised that the firm persist in prioritizing product quality, enhance its brand image, and maintain competitive pricing to sustain its competitiveness in the swiftly changing baking industry. Future studies may investigate the influence of advertising methods and customer behavior on decision-making in the food business.